PWE-086 The Role of Human Neutrophil Elastase and its Inhibitor Elafin In Ulcerative Colitis. (4th June 2013) - Kok, K; Curciarello, R; Biancheri, P; Langmead, L; MacDonald, T
Abstract : Introduction: Mucosal inflammation in ulcerative colitis (UC) is characterised by an influx of neutrophils which secrete large amounts of human neutrophil elastase (HNE), causing matrix degradation. They also produce the elastase-specific inhibitor, elafin. The aim of this study is to evaluate the relative production of elastase and elafin in active UC, and to investigate the modulatory effect of elafin on mucosal proteolytic activity ex vivo . Methods: We utilised intestinal biopsies from 18 patients with active UC and 12 non-UC healthy controls. Biopsies were homogenised and lysed to extract mucosal proteins. Proteolytic activity, using elastin as a substrate, was determined. Concentrations of elafin were measured using ELISA. The effect of protease inhibitors on proteolytic activity were determined in vitro using elafin, marimastat (matrix metalloproteinase inhibitor) and the synthetic elastase inhibitor, AAPV [N-(Methoxysuccinyl)-Ala-Ala- Pro-Val Chloromethyl Ketone]. The effect of elafin on proteolytic activity ex vivo was assessed by 24 hour organ culture in the presence and absence of elafin. Unpaired Student's t-test was used for statistical analyses. Results: Mucosal protein homogenates from patients with active UC displayed higher proteolytic activity in comparison to healthy controls ( p = 0.002). Elafin levels were increased in mucosal homogenates from active UC ( p = 0.007). The addition of elafin, marimastat or AAPV, in vitro, each diminished proteolytic activity. Organ culture of UC biopsies in the presence of elafin reduces the proteolytic activity of active UC ex vivo (n.s.). Conclusion: Colonic mucosal tissue from UC patients displays significantly higher elastinolytic activity in comparison to healthy controls. The addition of elafin has a restorative effect on the elastinolytic activity of UC mucosal homogenates, with the most notable effect in those tissues that had highest proteolytic activity. This occurs in the presence of significantly higher quantities of elafin in active UC mucosa. These data also show a beneficial modulatory effect of elafin on human gut tissue, suggesting a possible role for supplementary elafin in the treatment of UC. Disclosure of Interest: None Declared.